Climatic Regimes Based on Temperature and Rainfall in Nepal - Nayava, Janak Lal (Geographical Journal of Nepal, 2026)
Nepal, a small mountainous country extending from less than 100 m in the south to 8,848 m in the north, exhibits remarkable climatic diversity due to its rugged topography and east–west orientation. This study classifies climatic regimes based on mean monthly rainfall, and mean monthly maximum and minimum temperatures from 168 meteorological stations covering the period 1956–1975. Using the TAXON program (CSIRO) and a hierarchical, agglomerative, polythetic clustering method (MULCLAS), 35 standardized climatic attributes were analyzed to produce a DENDOGRAM identifying 30 distinct rainfall and temperature regimes. These were further consolidated into six major homo-climatic groups. The results reveal a strong altitudinal control on temperature regimes, with a mean lapse rate of approximately 6°C per kilometer, while rainfall patterns display greater spatial complexity, particularly in the central and western hill regions. The six major groups correspond broadly to three macroclimatic zones: subtropical (Terai and Inner Terai), warm temperate (Hill region), and cool temperate (Mountain region below 4,000 m). These zones reflect distinct thermal and moisture conditions that directly influence vegetation distribution, crop suitability, and agricultural potential. The classification provides a practical framework for crop breeding, agricultural planning, irrigation management, and the transfer of high-yielding varieties to climatically similar regions. Although based on mean climatic data, the study establishes a valuable baseline for understanding Nepal’s climatic diversity. The findings remain relevant for future climatic assessments using updated datasets and for broader applications in ecological and medicinal plant research.